In search of the good practices of personalized learning with ChatGPT for English test preparation - Fitria, Tira Nur (Erudita: Journal of English Language Teaching, 2025)
This research analyzes the good practices of ChatGPT as a supplementary tool for English test preparation. This research is a library research which used systemic literature review for the research method. This systemic literature review method highlights ChatGPT as a tool for preparing English proficiency tests like TOEFL, IELTS, and TOEIC. It offers features such as practice questions, test simulations, real-time feedback, and explanations. ChatGPT supports reading, writing, and speaking practice by generating comprehension questions, writing prompts, and conversational feedback. It helps users improve grammar, vocabulary, and coherence in writing while providing reading materials with summaries and vocabulary support. A key strength is its personalized approach, adapting materials to the learner’s level and progress. However, limitations include the inability to assess pronunciation accurately, provide certifications, or replicate real test pressure. Its responses may sometimes be inaccurate, and interactive feedback is limited. Therefore, for optimal results, users should combine ChatGPT with official test materials, real test simulations, and human guidance. The study highlights the need for further research and development to improve AI tools in language education.